Réponses

Meilleure réponse !
2014-05-13T13:34:39+02:00
Sachant que a = 6 et b = - 5/4
Calculer :
a - b    
3a - 2b    
(2 - b) / a      
1/a - 1/b

a - b
6 - 5/4
= 6 x 4 / 1 x 4 - 5/4
= 24/4 - 5/4
= 19/4

3a - 2b
3 * 6 - 2 * -5/4
= 18 + 10/4
= 18 x 4 / 1 x 4 + 10/4
= 72/4 + 10/4
= 82/4
= 2 x 41 / 2 x 2
= 41/2

(2 - b) / a
= (2 - -5/4) / 6
= (2 + 5/4) / 6
= (2 x 4 /1 x 4 + 5/4) / 6
= (8/4 + 5/4) / 6
= 13/4 : 6
= 13/4 x 1/6
= 13/24

1/a - 1/b
1/6 - 1 / -5/4
= 1/6 - 1 x - 4/5
= 1/6 + 4/5
= 1 x 5 / 6 x 5 + 4 x 6 / 5 x 6
= 5/30 - 24/30
= -19/30